Organizing Hajj Manasik as an Effort to Increase Knowledge of Hajj for Prospective Hajj Pilgrims at the Office of the Ministry of Religion of Enrekang Regency - Muna Muna; Amaluddin Amaluddin; Bustanul Iman RN (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the implementation of Hajj rituals as an effort to increase knowledge of Hajj for prospective Hajj pilgrims at the Ministry of Religion Office of Enrekang Regency. This type of research is qualitative; with approach; Qualitative. Research on the disclosure of problems as they are data collection techniques using observations, interviews, and documentation, using data analysis, namely; data presentation, data reduction, and conclusion drawing (verification). By testing and analyzing the data, namely: (1) credibility (internal validity), (2) transferability (external validity), (3) dependability (reliability), and (4) confirmability (objectivity). The results of this study indicate that the Hajj ritual implementation program as an effort to increase knowledge of the Hajj is starting from registration, guidance for Hajj rituals, guidance during the implementation of the Hajj in Saudi Arabia, repatriation, to coaching and guidance after the implementation of the Hajj. The learning method of Hajj rituals as an effort to increase knowledge of the Hajj for prospective pilgrims, namely the use of methods in guiding Hajj and Umrah through Hajj rituals can be of more than one kind (varies), including the lecture method, simulation method, and question and answer method. The supporting factors are; has a supervisor who is competent and experienced in guiding pilgrims, has adequate indoor facilities, has a collaboration between the Office of the Ministry of Religion of Enrekang Regency with health workers, has a strategic location. While the inhibitors are; lack of awareness of the pilgrims on the importance of all Hajj guidance materials, lack of outdoor facilities when practicing in the field, not having an organizational branch for the implementation of Hajj ritual guidance, and the absence of additional meetings or special schedules for Hajj pilgrims who missed the meeting.